2019
DOI: 10.1088/1741-4326/ab13e2
|View full text |Cite
|
Sign up to set email alerts
|

Implications of uncertainties on European DEMO design

Abstract: During the pre-conceptual design phase of fusion devices such as the European demonstration fusion power plant (DEMO), systems codes provide a fast evaluation of optimal design points and highlight high impact areas. However, determining or evaluating a design point at such an early stage comes with uncertainties in many of the design parameters. These uncertainties are both associated with the physics as well as the engineering basis of the European DEMO design. The work applies an uncertainty quantification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…On the other hand, the thermal He-4 fraction shows a linear increase in feasibility. These results may indicate that the plasma elongation should be at least 1.83 to fulfill the net electric power output constraint of 400 MW, and greater concentrations of thermal He-4 in the plasma are favorable to achieve the pulselength constraint of 2 h. In fact, it has been shown that greater fusion power is associated with larger elongations [6], and He-4 contributes to increase the energy confinement time when it does not exceed the dilution upper limit [25]. To visualize the combination effects on the feasibility space, the scatterplots of the plasma elongation against the thermal He-4 fraction are displayed on the top right and bottom left figures of Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, the thermal He-4 fraction shows a linear increase in feasibility. These results may indicate that the plasma elongation should be at least 1.83 to fulfill the net electric power output constraint of 400 MW, and greater concentrations of thermal He-4 in the plasma are favorable to achieve the pulselength constraint of 2 h. In fact, it has been shown that greater fusion power is associated with larger elongations [6], and He-4 contributes to increase the energy confinement time when it does not exceed the dilution upper limit [25]. To visualize the combination effects on the feasibility space, the scatterplots of the plasma elongation against the thermal He-4 fraction are displayed on the top right and bottom left figures of Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The parameters chosen were related to the physics in PROCESS rather than technological (such as efficiencies), as the next step attempts to understand how these uncertainties impact on the different plasma scenarios. To maintain similarity with previous studies, these parameters are present in [6] and are given as follows.…”
Section: Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…One approach to handle uncertainties is to use scaling relations (empirical or theoretical) and then vary the input parameters, such as plasma density, hypothetical confinement multipliers (e.g. H-factor), elongation etc and propagate through a systems code optimiser to see the impact on the design [87,88]. However, as mentioned earlier, caution is needed on the use of large multisource databases for choosing an optimum design of a particular device, and of course use of multipliers on scalings beyond the statistical spread has weak rigour.…”
Section: Types Of Uncertainty Their Implications and Managementmentioning
confidence: 99%